Radiotherapy management of brain metastases using conventional linear accelerator - Matzenauer, Marcel; Vrana, David; Vlachova, Zuzana; Cwiertka, Karel; Kalita, Ondrej; Melichar, Bohuslav (Biomedical papers, 2016)
Background and Aims: As treatments for primary cancers continue to improve life expectancy, unfortunately, brain metastases also appear to be constantly increasing and life expectancy for patients with brain metastases is low. Longer survival and improved quality of life may be achieved using localised radiological and surgical approaches in addition to low dose corticosteroids. Stereotactic brain radiotherapy is one rapidly evolving localized radiation treatment. This article describes our experience with stereotactic radiotherapy using a linear accelerator.Methods: We reviewed patients treated with stereotactic radiotherapy, from the time of its introduction into daily practice in our Department of Oncology in 2014. We collected the data on patient treatment and predicted survival based on prognostic indices and actual patient outcome.Results: A total of 10 patients were treated by stereotactic radiotherapy, in one case in combination with whole brain radiotherapy and hippocampal sparing. There was no significant treatment related toxicity during the treatment or follow-up and due to the small number of fractions, the overall tolerance of the treatment was excellent. The patient intrafractional movement in all cases was under 1 mm suggesting that 1 mm margin around the CTV to create the PTV is sufficient and also that patient immobilization using the thermoplastic mask compared with invasive techniques, is feasible. We also found that prognostic indices such as the Graded Prognostic Assessment provide accurate predictions of patient survival.Conclusions: Based on our current evidence, patients with brain metastases fit enough, should be considered for stereotactic radiotherapy treatment.
Keywords: brain; metastases; stereotactic; radiosurgery; radiotherapy; treatment